The Comparative Analysis of Mudik Mode Transportation: A Case of PT Adirona Nirmana Lestari Employer, Indonesia - Muhamad Fauzi Apriansyah; Andri Irfan Rifai; Susanty Handayani (Indonesian Journal of Multidisciplinary Science, 2022)
Public transportation is a service to move people or goods to support mobility from one place to another. The use of public transportation is still one of the favorite transportation for migration from village to City or from City to village (mudik). Homecoming has become one of the traditions that occur every year in Indonesia. However, the increase in the number of public transportation passengers ahead of homecoming makes it challenging to get tickets and public transportation, so it is necessary to find alternative transportation so that homecoming is still carried out. The purpose of making this paper is to find out the factors that affect PT. Adirona Nirmana Lestari (ANL) is sustainable in selecting homecoming (mudik) transportation between buses and motorbikes. The method is to spread the questionnaire to 100 respondents, and then the questionnaire result data is analyzed using the spider chart method. The results showed that of the ten parameters asked in the questionnaire, the parameter greatly influenced the selection of homecoming transportation for ANL employees was the cost of travel.